The bidual of r-algebras - Yilmaz, R. (Український математичний журнал, 2011)
We prove that the order continuous bidual of an Archimedean r-algebra is a Dedekind complete r-algebra with respect to the Arens multiplications. Доведено, що порядковий неперервний бiдуал архiмедової r-алгебри є повною r-алгеброю Дедекiнда вiдносно множень Аренса.